PENGUKURAN TINGKAT KESUKSESAN SISTEM INFORMASI RUANG MAHASISWA PADA UNIVERSITAS BSI PSDKU SUKABUMI DENGAN MODEL DELONE DAN MCLEAN - Jamal Maulana Hudin; Yusti Farlina; Denny Pribadi (Program Studi S1 Sistem Informasi Fakultas Komputer dan Teknik Universitas Alma Ata, 2019)
Measurement of student satisfaction rate of Student room information system is the benchmark of how much the institution contribution to provide facilities in academic service. Model Delone & Mclean is a model that can measure the satisfaction level of information system, with independent variables of system quality, quality of information and quality of service that will affect the dependent variables of use and User satisfaction. The type of research conducted is quantitative research with the number of respondents 174 students as samples, with simple random sampling technique. The results showed that the value of R2 was 0.934 or 93% for user satisfaction variables and 0.585 or 0.6% for usage variables, with a value of coherent determinations approaching 1, then it can be interpreted that the model enters into criteria Substantial. Value DF = 174 – 6 = 168 and a = 10%, then T-table value 1.28, then obtained 4 hypotheses supported, namely the quality of information on user satisfaction of 1.57, quality of service to user satisfaction of 2.33, the quality of the system to satisfaction Users and usage of 8.49 and 4.43. It can be interpreted that the student room information system of BSI PSDKU Sukabumi University has been successfully applied mainly in the quality of information system